Overt and Null Subject Variation in Ammani Arabic: Distribution, Constraints, and Implications - Khater, Rahaf; Jarrah, Marwan; Al-Badawi, Mohammad; Al-Shawashreh, Ekab (Psiholìngvìstika, 2024)
Purpose. This article investigates the distribution of overt and null subject pronouns in Ammani Arabic (AA) from a variationist perspective, identifying social and linguistic constraints that shape pronoun expression. The study examines how age, gender, and educational attainment, alongside grammatical person, sentence polarity (positive vs. negative), tense, clause type (root vs. embedded), and verbal component (verbal vs. verbless), impact the choice between overt and null pronouns. Methods. The analysis draws on a dataset of 32 sociolinguistic interviews, totaling over 32 hours of recorded data. Each interview was coded to capture both social factors and syntactic environments that affect pronoun usage. Using distributional and multivariate statistical methods, the study reveals the systematic structures underlying pronoun variation in AA. Results. Findings show that pro-drop in AA is significantly influenced by both social and linguistic factors. Socially, age and gender play key roles in pronoun use, reflecting strong links between pronoun choice and demographic identity. Linguistically, factors like verbal component, clause type, polarity, and grammatical person are crucial in determining the choice between overt and null pronouns, establishing predictable and structured patterns in pronoun expression. This variation is shown to be rule-governed rather than random. Conclusions. The study demonstrates that pro-drop in AA follows structured, rule-based patterns shaped by identifiable social and linguistic constraints. This research enriches the understanding of subject pronoun variation in Arabic dialects, underscoring the value of variationist analysis in exploring how social meaning and linguistic structure intersect. The findings offer broader implications for understanding pronoun variation in language varieties globally, with a focus on social indexing within Arabic dialects.